AtBET5 is essential for exine pattern formation and apical meristem organization in Arabidopsis. (September 2018) - Zhang, Jin; Chen, Jun; Wang, Lijuan; Zhao, Shutang; Li, Jianbo; Liu, Bobin; Li, Hongying; Qi, Xingyun; Zheng, Huanquan; Lu, Mengzhu
Highlights: Pollen grains of the Arabidopsis atbet5 mutant reduced fertility. AtBET5 is involved in apical meristematic organization. Auxin response in root tip cells is altered by AtBET5. Abstract: BET5 is a component of trafficking protein particle (TRAPP) which has been studied extensively in non-plant organisms where they are involved in membrane trafficking within Golgi and between Golgi and early endosomes. Recent analysis of TRAPP in different classes of organisms indicates that TRAPP function might exhibit differences among organisms. A single copy of the BET5 gene named AtBET5 was found in the Arabidopsis genome based on sequence similarity. Developmental phenotype and the underlying mechanisms have been characterized upon transcriptional knock-down lines generated by both T-DNA insertion and RNAi. Pollen grains of the T-DNA insertional line present reduced fertility and pilate exine instead of tectate exine. Perturbation of the AtBET5 expression by RNAi leads to apical meristematic organization defects and reduced fertility as well. The reduced fertility was due to the pollination barrier caused by an altered composition and structure of pollen walls. Auxin response in root tip cells is altered and there is a severe disruption in polar localization of PIN1-GFP, but to a less extent of PIN2-GFP in the root tips, which causes the apical meristematic organization defects and might also be responsible for the secretion of sporopollenin precursor or polar targeting of sporopollenin precursor transporters.